2022
DOI: 10.3126/janr.v5i1.50362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mulch materials on potato production and soil properties in high hill of Parbat, Gandaki Province, Nepal

Abstract: An experiment for two consecutive years (2017 and 2018) was conducted to evaluate the use of mulching materials in increasing productivity and profitability of potato production. The experiment was conducted in Randomized Complete Block Design (RCBD) with five different mulching materials including control replicated for four times namely, banmara (Agertina adenophora) weed (T1), black polythene sheet (T2), white polythene sheet (T3), commercially used mulch paper having black color outside and silver color in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In a study by Bhatta et al (2020), they have reported the lower soil temperature in white and silver plastic mulch than black plastic mulch in potato. Timilsina et al (2022) have reported the significant differences in yield attributing traits in plastic mulching treatment. In this study, we measured the highest plant height in straw mulch treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Bhatta et al (2020), they have reported the lower soil temperature in white and silver plastic mulch than black plastic mulch in potato. Timilsina et al (2022) have reported the significant differences in yield attributing traits in plastic mulching treatment. In this study, we measured the highest plant height in straw mulch treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Upadhyaya et al (2020), found significantly higher yield of potato with the application of biochar. The application of biochar significantly increased the biomass, root, and shoot yields of radish (Timilsina et al, 2017).…”
Section: Effect Of Biochar On Crop Production and Productivitymentioning
confidence: 99%
“…The effect of biochar on available P may vary, depending on the rate of biochar, soil type and soil acidic conditions. Timilsina et al (2017) reported significantly higher soil pH, including other soil properties such as soil organic matter, total nitrogen, available phosphorus, and available potassium with the addition of biochar. Furthermore, Jaishi, 2020 found that application of UCB improved soil chemical properties.…”
Section: Changes In Soil Properties Due To Biochar Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…These include cation or anion exchange reactions and adsorption of NH3 or organic N on biochar (Clough et al, 2013). The addition of biochar to soil leads to increase of the soil pH, soil organic matter, soil bulk density, total nitrogen, available phosphorus and available potassium contents of soil (Syuhada et al, 2016;Timilsina et al, 2017;Mierzwa-Hersztek et al, 2019). Biochar has the potential to improve physical as well as chemical soil properties, due to biochar properties related to surface area and porosity, carbon content, nutrient content and cation exchange capacity (CEC) (Carvalho, 2015).…”
Section: Introductionmentioning
confidence: 99%